Building Children's Character Through The Pancasila Student Profile Strengthening Project At Tk It Al-Kiswah Bengkulu City - Sari, Ayu Puspita; Nirwana, Evi Selva (Peneliti.net, 2025)
This study aims to examine character building through the pancasila student profile strengthening project at TK IT Al-Kiswah, Bengkulu City. The research subjects were classroom teachers and children from Class B III Ummar Khayyam. This research used a descriptive qualitative approach, in which the data were presented in detailed and in-depth narrative form. Data collection techniques included observation, interviews, and documentation. The results show that building children’s character through the pancasila student profile strengthening project at TK IT Al-Kiswah has been effective in fostering character values through learning activities with the theme “Imagination and Creativity”. This project has played an important role in instilling character values such as religiousness, honesty, responsibility, discipline, hard work, tolerance, collaboration, global diversity, creativity, faith, piety, and independence, although critical reasoning skills still need to be improved. Thus, the Pancasila Student Profile Strengthening Project at TK IT Al-Kiswah has proven effective in shaping children’s character from an early age.